The Effect of Capital Structure, Profitability and Liquidity on the Company's Value in the Automotive Sub-Sector and Components for the Period 2017-2021 - Hasanudin Hasanudin (Institute of Computer Science (IOCS), 2022)
This research was conducted to determine the influence of Capital Structure, Profitability and Liquidity on Company Value using company time series panel data with a research period of 2017-2021. Using the panel data linear regression analysis method, with a sample of 9 companies from 13 automotive and component sub-sector companies in Indonesia. This research was analyzed using E views version 9 software with the results of the study, namely the capital structure proxiated by Debt Equity Ratio (DER) has a positive and significant effect on the Company's Value which is proxikan with Price to Book Value (PBV), Profitability produced by Return On Asset (ROA) has a negative and significant effect on the value of the Company proxikan with Price to Book Value (PBV) and Liquidity proxikan with Current Ratio (CR) have a positive and insignificant effect on the value of companies proxistivated with Price to Book Value (PBV).